Comparison of Phenolic Glycolipid 1 Antibody Levels in Household Contacts of Pausibasilary and Multibacilary Patients - Febrina Andarini; Rusmawardiana; Soenarto Kartowigno; Erial Bahar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Abstract Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae (M. leprae). Distribution of leprosy cases in the world in 2015 was highest in the Southeast Asia region, with 156,118 cases. The increase in new cases and the high prevalence of leprosy requires action to break the chain of transmission. Household contact groups are easy to identify by the research group, because the group has good reasons for examining or getting chemoprophylaxis. Objectives: Our objective was to compare Phenolic Glycolipid 1 (PGL-1) antibody levels in household contacts of pausibasilary (PB) and multibacilary (MB) patients. Methods: This study was a analytic observational study with a cross-sectional design. ELISA examination will be conducted at the Leprosy Laboratory of the Institute of Tropical Diseases, Airlangga University, Surabaya. The study was conducted from 3 December 2019 to 31 January 2020, with a total sample of 60 samples. Resuls: PGL-1 antibodies in MB leprosy household contact were greater than PGL-1 antibodies in PB leprosy household contact, and the results showed statistically significant (p = 0.011). Conclusions: There are differences in the levels of PGL-1 antibodies between household contact PB leprosy patients and MB. The household contact PGL-1 antibody levels in MB leprosy are greater than PB leprosy.